PENGUJIAN BUKTI PERMULAAN YANG CUKUP DALAM PENETAPAN TERSANGKA MELALUI LEMBAGA PRAPERADILAN - Setiyono, Setiyono (Lex Jurnalica, 2024)
AbstractThe determination of suspect status against a person suspected of committing a criminal act must of course be based on the condition in the form of preliminary evidence that is the basis for the issuance of a Decree on the Determination of Suspect. If we re-read the Criminal Procedure Code (KUHAP) carefully and thoroughly, in relation to the phrase preliminary evidence, there are three types or categories of nomenclature used in KUHAP, namely the phrase initial evidence, the phrase sufficient evidence or sufficient evidence, and the phrase sufficient preliminary evidence. Regarding the determination of a suspect, sufficient preliminary evidence is used as one of the benchmark variables by the investigator as the basis for exercising discretion to declared a person as a suspect. In its development, the use of sufficient preliminary evidence as a basis to declared a person as a suspect in a criminal case can be tested for its validity in a pre trial institution. The formulation of the problem in this paper is whether the benchmark in testing sufficient preliminary evidence in the determination of the Suspect through a pre trial institution and whether there are restrictions or limitations to test sufficient preliminary evidence in the determination of the Suspect in the pre trial examination. The type of research used is normative, using the approach of laws and other regulations. The nature of the research is descriptive, using secondary data. The research analysis was carried out in a qualitative way and a deductive method of drawing conclusions. Regulations and other legal sources such as the KPK Law, MKRI Decision Number 21/PUU-XII/2014 and Perkabareskrim Number 1 of 2022 have provided a clear benchmark formulation regarding sufficient preliminary evidence to be used as a basis in providing the determination of a suspect to a person suspected of committing a criminal act through a Decree on the Determination of a Suspect. The benchmark for testing sufficient preliminary evidence is the existence of at least 2 (two) pieces of evidence, both those regulated in the provisions of Article 184 paragraph (1) of KUHAP and electronic evidence. In addition, there is a limit to the testing of sufficient preliminary evidence in the determination of the suspect in the pre trial examination, namely the limit of quantitative sufficiency in the form of a minimum number of 2 (two) evidence and the limit of qualitative sufficiency in the form of a tempus for making a witness BAP as preliminary evidence which should ideally be done before the tempus for determining the suspect.Keywords: Sufficient preliminary evidence, Determination of suspects, Pre Trial.AbstrakPenetapan status tersangka terhadap seseorang yang diduga sebagai pelaku tindak pidana tentunya harus didasarkan pada syarat berupa adanya bukti permulaan yang menjadi dasar untuk diterbitkannya Surat Ketetapan tentang Penetapan Tersangka. Apabila membaca kembali KUHAP secara cermat dan teliti maka berkaitan dengan frasa bukti permulaan terdapat 3 (tiga) jenis atau kategori nomenklatur yang digunakan dalam KUHAP yaitu frasa bukti permulaan, frasa cukup bukti atau bukti yang cukup dan frasa bukti permulaan yang cukup. Berkaitan dengan penetapan tersangka maka bukti permulaan yang cukup digunakan sebagai salah satu variabel tolok ukur oleh penyidik sebagai dasar alasan melaksanakan diskresi untuk menetapkan seseorang sebagai tersangka. Pada perkembangannya maka penggunaan bukti permulaan yang cukup sebagai dasar untuk menetapkan seseorang sebagai tersangka dalam suatu perkara pidana dapat dilakukan pengujian keabsahannya dalam lembaga praperadilan. Rumusan permasalahan dalam tulisan ini adalah apakah tolok ukur dalam menguji bukti permulaan yang cukup dalam penetapan Tersangka melalui lembaga praperadilan dan apakah ada pembatasan atau limitasi untuk menguji bukti permulaan yang cukup dalam penetapan Tersangka pada pemeriksaan praperadilan. Tipe penelitian yang digunakan adalah normatif, dengan menggunakan pendekatan Undang-Undang dan regulasi lainnya. Sifat penelitian deskriptif, dengan menggunakan data sekunder. Analisis penelitian dilakukan dengan cara kualitatif dan metode penarikan kesimpulan secara deduktif. Regulasi dan sumber hukum lainnya seperti UU KPK, Putusan MKRI Nomor 21/PUU-XII/2014 dan Perkabareskrim Nomor 1 Tahun 2022 telah memberikan rumusan tolok ukur yang jelas mengenai bukti permulaan yang cukup untuk digunakan sebagai dasar dalam memberikan penetapan tersangka kepada seseorang yang diduga melakukan tindak pidana melalui Surat Ketetapan tentang Penetapan Tersangka. Adapun tolok ukur pengujian bukti permulaan yang cukup adalah adanya minimal 2 (dua) alat bukti baik yang diatur dalam ketentuan Pasal 184 ayat (1) KUHAP maupun alat bukti elektronik. Selain itu, terdapat adanya limitasi pengujian bukti permulaan yang cukup dalam penetapan tersangka pada pemeriksaan praperadilan, yaitu limitasi kecukupan secara kuantitatif berupa jumlah minimum 2 (dua) alat bukti dan limitasi kecukupan secara kualitatif berupa tempus pembuatan BAP saksi sebagai bukti permulaan yang idealnya dilakukan sebelum adanya tempus penetapan tersangka.Kata kunci : Bukti Permulaan Yang Cukup, Penetapan Tersangka, Praperadilan.